Adapting Kurikulum Merdeka books with Islamic values: a case study at SDIP Ummul Mukminin - Ma’rifatu Ambiya (Hipkin Journal of Educational Research, 2026)
Since the Kurikulum Merdeka was implemented, Islamic-based schools face unique demands to contextualize educational content with moral and religious teachings without compromising national learning standards. Within this dynamic, curriculum flexibility becomes a crucial factor for successful adaptation, allowing schools to develop operational strategies that align with their identity and the needs of their students. This study investigates how SDIP Ummul Mukminin adapts Kurikulum Merdeka books through the lens of Islamic value integration, resource utilization, and institutional support systems. Using a descriptive qualitative method, data were gathered through interviews with school staff and document analysis. The findings reveal that book selection is guided by curriculum alignment and potential for religious contextualization, while material adaptation involves supplementary modules and analogies. The school library supports learning by providing both digital and printed resources with technological enhancements. This research highlights the adaptive strategies employed by faith-based schools and underscores the need to refine policies and train teachers in curriculum implementation.   Abstrak Sejak Kurikulum Merdeka diterapkan, sekolah berbasis Islam menghadapi tuntutan unik untuk mengontekstualisasikan konten pendidikan dengan ajaran moral dan agama tanpa mengorbankan standar pembelajaran nasional. Dalam dinamika ini, fleksibilitas kurikulum menjadi faktor penting untuk adaptasi yang berhasil, yang memungkinkan sekolah untuk mengembangkan strategi operasional yang selaras dengan identitas mereka dan kebutuhan murid mereka. Studi ini menyelidiki bagaimana SDIP Ummul Mukminin mengadaptasi buku-buku teks Kurikulum Merdeka melalui lensa integrasi nilai-nilai Islam, pemanfaatan sumber daya, dan sistem pendukung kelembagaan. Dengan menggunakan metode kualitatif deskriptif, data dikumpulkan melalui wawancara dengan staf sekolah dan analisis dokumen. Temuan penelitian mengungkapkan bahwa pemilihan buku teks dipandu oleh keselarasan kurikulum dan potensi kontekstualisasi keagamaan, sementara adaptasi materi melibatkan modul dan analogi tambahan. Perpustakaan sekolah mendukung pembelajaran dengan menyediakan sumber daya digital dan cetak dengan peningkatan teknologi. Penelitian ini menyoroti strategi adaptif yang digunakan oleh sekolah berbasis agama dan menggarisbawahi perlunya penyempurnaan kebijakan dan pelatihan guru dalam implementasi kurikulum. Kata Kunci: buku teks; integrasi nilai Islam; Kurikulum Merdeka